Effects of formulation composition on hardness and friability of okara tablet using different chemometric methods - Mohamad Zen, Nur Izzati (2016)
The usage of soy is keep on increasing year by year. It increases the problem of financial crisis and environmental pollution due to large amount of waste produced every year. Therefore, the nutrients of soy residue called Okara were studied and developed to become a beneficial waste. The used Okara was dried using a freeze dryer at -105°C to avoid from microbial growth which may cause contamination. The results of proximate analysis show that, the dried Okara contain about 21.78±1.06% of protein, 3.43±0.22% of fats, 15.82±0.79% of fiber, 3.53±0.12% of ash and 10.87±0.55% of moisture. The total phenolic content (antioxidant) in Okara is 0.86±0.39 GAE mg/100g of Okara. The major aim of this study is to investigate the effect of ingredient towards the tablet physical properties. The Okara tablets were produced using the direct compression method. Four inputs were studied; the percentage of Okara (A), maltodextrin (B), guar gum (C) and microcrystalline cellulose (D) toward the tablets‘ hardness and friability using three statistical software methods; D-optimal mixture design, artificial neural network (ANN), and wavelet neural network (WNN). For comparison study of D-optimal mixture design, ANN and WNN, data sets from mixture design were adopted for predicting the hardness and friability of tablet based on optimal composition ingredient which are 30.608% of A, 15.000% of B, 5.764% of C, and 46.628% of D. Based on RMSE, R2, and AAD values, ANN has shown the topology of GA which gave the best performance in both hardness and friability studies. The best architecture of hardness response is GA-4-12-1 with importance of variables; 24.79% of A, 27.45% of B, 22.37% of C, and 25.39% of D. On the other hand, the best architecture of friability response is GA-4-1-1 with importance of variables; 10.59% of A, 2.73% of B, 18.49% of C, and 68.49% of D. The order of overall prediction ability for hardness response is ANN-GA>MD>WNNGA, while for friability response is ANN-GA>WNN-GA>MD. Finally for safety procedure, heavy metal tests and microbiological tests were carried out. The results show satisfactory level for both heavy metals and microbes. Thus, the Okara tablet formulation was successfully optimized using different chemometric method and excellent for nutraceutical industry.